Antibiotic stewardship in a tertiary care NICU of northern India: a quality improvement initiative. (3rd August 2021) - Agarwal, Sunita; Patodia, Jyoti; Mittal, Jaikrishan; Singh, Yatish; Agnihotri, Vaibhav; Sharma, Varun
Abstract : Background: The overuse of antibiotics in newborns leads to increased mortality and morbidities. Implementation of a successful antibiotic stewardship programme (ASP) is necessary to decrease inappropriate use of antibiotics and its adverse effects. Problem: Our neonatal intensive care unit (NICU) is a tertiary referral centre of north India, consisting of all outborn babies mostly with sepsis caused by high rate of multidrug-resistant organisms (MDROs). So antibiotics are not only life-saving but also used excessively with a high antibiotic usage rate (AUR) of 574 per 1000 patient days. Method: A quality improvement (QI) study was conducted using the Plan–Do–Study–Act (PDSA) approach to reduce AUR by at least 20% from January 2019 to December 2020. Various strategies were made : such as making a unit protocol, education and awareness of NICU nurses and doctors, making check points for both starting and early stoppage of antibiotics, making specific protocol to start vancomycin, and reviewing yearly antibiotic policy as per antibiogram. Results: The total AUR, AUR (culture negative) and AUR (vancomycin) was reduced by 32%, 20% and 29%, respectively, (p<0.01). The proportion of newborns who never received antibiotics increased from 22% to 37% (p<0.045) and the proportion of culture-negative/screen-negative newborns where antibiotics were stopped within 48 hours increased from 16% to 54% (p<0.001). The compliance with the unit protocol in starting and upgrading antibiotic was 75% and 82%, respectively. In early 2020, there was a sudden upsurge in AUR due to central line-related bloodstream infection breakout. However, we were able to control it, and all the PDSA cycles were reinforced. Finally, we could reattain our goals, and also able to sustain it until next 1 year. There was no significant difference in overall necrotising enterocolitis and mortality rates. Conclusion: In a centre such as ours, where sepsis is a leading cause of neonatal deaths, restricting antibiotic use is a huge challenge. However, we have demonstrated implementation of an efficient ASP with the help of a dedicated team and effective PDSA cycles. Also, we have emphasised the importance of sustainability in success of any QI study.